1964
DOI: 10.1901/jeab.1964.7-285
|View full text |Cite
|
Sign up to set email alerts
|

BRAIN‐STIMULATION INTENSITY, RATE OF SELF‐STIMULATION, AND REINFORCEMENT STRENGTH: AN ANALYSIS THROUGH CHAINING1

Abstract: Reinforcement strengths of different intensities of brain stimulation were assessed by means of a two-member behavioral chain. A variable interval schedule of 30 sec was the first-member, and five lever presses, each rewarded with stimulation, was the second. It was found that response rate on the VI schedule continued to increase beyond the intensity value which produced peak rate on the second-member, self-stimulation lever. It was concluded (1) that brain-stimulation reinforcement strength cannot be assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

1965
1965
2004
2004

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…however, see Hodos and Valenstein, 1962;Hawkins and Pliskoff, 1964) and second member schedule performance, our analyses of the 0L 10 mIN Fig. 9.…”
Section: The 24-hr Sessionsmentioning
confidence: 85%
“…however, see Hodos and Valenstein, 1962;Hawkins and Pliskoff, 1964) and second member schedule performance, our analyses of the 0L 10 mIN Fig. 9.…”
Section: The 24-hr Sessionsmentioning
confidence: 85%
“…The presentation of ascending or descending current intensities during ICSS produces, respectively, positive or negative contrast effects [21,28,57]. It has been shown that reward thresholds are lower during the presentation of an ascending current series, in comparison to random or descending current series [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been successful in making behavior reinforced by an ICS more closely resemble behavior reinforced by food (Gibson, Reid, Sakai, & Porter, 1965;Hawkins & Pliskoff, 1964;Pliskoff, Wright, & Hawkins, 1965). For example, it had long been considered difficult or impossible to maintain behavior reinforced by an ICS on the types of intermittent schedules often employed with food-especially when these schedules allowed only for infrequent reinforcement.…”
Section: Methodsmentioning
confidence: 99%